PEMAKNAAN PENERAPAN AKUNTANSI BASIS AKRUAL - Yanni Yanni; Fransiskus Randa; Yakobus K Bangun (Magister Akuntansi, Universitas Atma Jaya Makassar, 2020)
This study is a qualitative study of the application of the accrual-based Government accounting system to the Government of North Toraja Regency. The purpose of this study is to interpret the application of accrual-based Government Accounting Standards (SAP) to the Government of North Toraja Regency. Data in this study were collected through observation, documentation, and interviews with five informants directly related to the implementation of accrual-based Governent Accoutning Standards (SAP). The data that has been collectted is then analyzed and interpreted by qualitative methods using an interpretive approach. The results showed that the application of accrual-based Government Accounting Standards (SAP) in the North Toraja Regency Government was a reflection of a formality. This is supported by the existence of government regulations that require all local governments including the North Toraja Regency Government to implement accrual-based Government Accoutning Standards. The complexity of the financial statements is a major factor in the resistance attitude of the North Toraja Regency financial management in the accrual-based Government Standard implementation. Meanwhile, in terms of organizational culture, the North Toraja Regency Government is required to apply accrual-based Government Accounting Standards